2016
DOI: 10.21608/jbaar.2016.108746
|View full text |Cite
|
Sign up to set email alerts
|

A study on the possible role of date fruit on the electrophysiology and neuropathic changes in diabetic polyneuropathy.

Abstract: Diabetes mellitus (DM) is a chronic metabolic disease with many neurovascular complications particularly diabetic peripheral neuropathy (DPN) that is mostly developed secondary to much release of reactive oxygen species (ROS, the potential mediators of DM-induced oxidative stress). The aim of the present study is to evaluate the possible neuroprotective role of Date Fruit Extract (DFE), an antioxidant nutrient, in ameliorating the DPN in streptozotocin-induced diabetic rats. Forty adult male rats were used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…It is plausible that genistein, a flavonoid found in dates reduces β-cells apoptosis, increases β-cells number, promotes β-cells survival in pancreatic islets and preserves islets mass, subsequently increasing insulin secretion while reducing glucose levels due to activated liver-pyruvate kinase [55]. In another six-week in vivo study, Bendary et al [56] evaluated glucose, insulin and HbA1c levels in albino rats (n = 40). At the end of experiment, they found that serum glucose, insulin and HbA1c levels were 133.2 ± 7.2 mg/dL, 9.0 ± 0.2 µ/mL and 0.53 ± 0.02 mg/g Hb, respectively for date fruit extract-treated group as compared to 299.6 ± 16.7 mg/dL, 8.9 ± 0.7 µU/mL and 0.9 ± 0.05 mg/g Hb for untreated group (p < 0.05).…”
Section: Physicochemical and Nutritional Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that genistein, a flavonoid found in dates reduces β-cells apoptosis, increases β-cells number, promotes β-cells survival in pancreatic islets and preserves islets mass, subsequently increasing insulin secretion while reducing glucose levels due to activated liver-pyruvate kinase [55]. In another six-week in vivo study, Bendary et al [56] evaluated glucose, insulin and HbA1c levels in albino rats (n = 40). At the end of experiment, they found that serum glucose, insulin and HbA1c levels were 133.2 ± 7.2 mg/dL, 9.0 ± 0.2 µ/mL and 0.53 ± 0.02 mg/g Hb, respectively for date fruit extract-treated group as compared to 299.6 ± 16.7 mg/dL, 8.9 ± 0.7 µU/mL and 0.9 ± 0.05 mg/g Hb for untreated group (p < 0.05).…”
Section: Physicochemical and Nutritional Compositionmentioning
confidence: 99%
“…As a result, there is inhibition of the production of reactive oxygen species, which help to prevent oxidative stress and stimulate Schwann cells to produce nerve growth factors, helpful for neuronal support [61]. Similarly, Bendary et al [56] also observed neuroprotective activities of date palm fruit, although the mechanism was unclear.…”
Section: Neuroprotective Activitymentioning
confidence: 99%